Does This Robot Make Me Look Smart? How the Addition of a Robotic Pet Influences First Impressions. (September 2013) - Halse, Shane E.; Lum, Heather C.; Sims, Valerie K.; Winkelbauer, Christine A.; Harris, Megan A.
The current study examined whether the addition of either a robotic cat or a robotic dog to the picture of a male or female model, could affect the participants first impressions of the model. The participants were directed to a website and randomly assigned to a picture. Next, they answered a survey related to their perceptions of the model. Individual differences including participant gender, entity type, and response on robot attitudes scale were found. The results indicate that the items around or with us can be particularly important in public and social settings where first impressions can be the only ones a person gets to make.